Inflation (de-)anchoring in the euro area - Valentin Burban; Bruno De Backer; Andreea L. Vladu (European Central Bank (ECB), 2024)
This article measures the degree of potential de-anchoring of inflation expectations in the euro area vis-à-vis the inflation objective of the European Central Bank (ECB). A no-arbitrage term structure model that allows for a time-varying long-term mean of inflation expectations, π∗t , is applied to inflation-linked swap (ILS) rates, while taking into account survey-based inflation forecasts. Estimates of π∗t have been close to 2% since the mid-2000s, indicating that long-term inflation expectations have overall remained well anchored to the ECB's inflation objective. As this objective is however related to the "medium term", expectations components of various forward ILS rates are extracted: they appear to have been broadly anchored, with tentative signs of de-anchoring up to the two-year horizon. Using backcasted ILS rates, estimates of π∗t are much above 2% in the early 1990s, but they convergence to levels below 2% by the end of the decade when the ECB was established.
Keywords: E31; E43; E47; E58; 330; Inflation-linked swap rates; surveys; no-arbitrage; shifting endpoint; inflation expectations